The effect of college education on health - Kasey Buckles; Ofer Malamud; Melinda Sandler Morrill; Abigail Wozniak (Institute for the Study of Labor (IZA), 2012)
We exploit exogenous variation in college completion induced by draft-avoidance behavior during the Vietnam War to examine the impact of college completion on adult mortality. Our preferred estimates imply that increasing college completion rates from the level of the state with the lowest induced rate to the highest would decrease cumulative mortality by 28 percent relative to the mean. Most of the reduction in mortality is from deaths due to cancer and heart disease. We also explore potential mechanisms, including differential earnings, health insurance, and health behaviors, using data from the Census, ACS, and NHIS.
Keywords: I12; I23; J24; 330; health; college education; Bildungsabschluss; Hochschule; Gesundheit; Gesundheitsvorsorge; USA